Concentration and excitation effects on the exciton dynamics of poly(3-hexylthiophene)/PbS quantum dot blend films - Tsokkou, Demetra; Itskos, Grigorios; Choulis, Stelios A.; Yarema, Maksym; Heiss, Wolfgang; Othonos, Andreas (My University, 2013)
The dynamics of photoexcitations in hybrid blends of poly(3-hexylthiophene) (P3HT) conjugated polymer donor and oleic-acid capped lead sulfide (PbS) quantum dot (QD) acceptors of different concentrations - for light harvesting applications - were investigated using time-resolved transmission and photoluminescence spectroscopies. Following excitation at 400 nm and probing in the 500-1000 nm region, we find that geminate excitation recombination in the blend of P3HT/PbS QDs dominates the transient decays at sub-ns times while intermaterial interactions such as charge transfer processes appear at longer times in the 1-50 ns regime. For the hybrid blend films with lower QD concentrations (<67% wt), polymer exciton recombination dominates the overall transient absorption signal. For higher QD contents, QD state relaxation effects become visible. Excitation density studies reveal the presence of linear exciton relaxation effects in the P3HT region while carrier decay for films with high PbS QD concentration is influenced by QD Auger recombination. Time-resolved luminescence shows that electron transfer from the P3HT/PbS QDs appears relatively inefficient in comparison to the geminate recombination, while hole transfer competes favorably to intrinsic QD recombination.
Keywords: Heterojunction solar-cells; Colloidal pbS nanocrystals; Organic photodiodes; Charge-separation; Electron-transfer; Polymer; Fullerene; Spectroscopy; P3HT/PCBM